Evaluation of Transaction Cost of Unlawful Business in Southern Thailand - Achariya, Chinasak Suwan; Leesahad, Tasanee (Richtmann Publishing, 2011)
This research aimed to evaluate transaction cost on trade cycle a type of illegal oil between Thailand -Malaysia borders atSadao Customs Checkpoint, Sadao District, Songkhla Province relating to the trading network of illegal oil, Nathawee District,Songkhla Province and to study certain influence of transaction cost per marginal expenditure for the import of illegal one. Besides, theresearch found that entrepreneur’s the import procedure of illegal oil was the key factor which were occurred special expenditure aboutcustoms official and interception point official’s benefits as well as transaction cost, finally, caused marginal expenditure increasedalso.Transaction cost on entrepreneur’s the import procedure of illegal oil expended more less approximately 1% of total expenditure,effecting therefore entrepreneurs were able to make a high profitable business in each month. As a result, the research discovered that stepsreduced the import of illegal oil, this operation must result to the higher transaction cost and it will be carried out by the informationtechnology systems to manage inventory turnover systems including as open systems that allowed public sectors or association of oil tradingbusiness in own province participated to operate with policies administration.